Nonsteroidal antiinflammatory drugs and treatment of cystoid macular edema : Nesteroidni protuupalni lijekovi u liječenju cistoidnog makularnog edema - Bilen Babić, Marijana (Array, 2019)
Nonsteroidal antiinflammatory drugs (NSAIDs) have become a significant therapeutic adjunctive tool in the routine and complicated intraocular surgery. Topical NSAIDs prevent intraoperative miosis, reduce pain, postoperative inflammation and incidence of cystoid macular edema (CME). Although there is no established protocol for prophylaxis of pseudophakic CME, due to the relationship between proinflammatory prostaglandins and CME, using corticosteroids and NSAIDs could prevent CME. NSAIDs have a synergistic antiinflammatory effect with steroids, but can also be used alone when corticosteroid therapy could be harmful. Prospective clinical trials need to define treatment protocol for topical NSAIDs use, due to their powerful influence to prevent perioperative complications.